Astatine-211-Labeled Gold Nanoparticles for Targeted Alpha-Particle Therapy via Intravenous Injection - Xuhao Huang; Kazuko Kaneda-Nakashima; Yuichiro Kadonaga; Kazuya Kabayama; Atsushi Shimoyama; Kazuhiro Ooe; Hiroki Kato; Atsushi Toyoshima; Atsushi Shinohara; Hiromitsu Haba; Yang Wang; Koichi Fukase (MDPI AG, 2022)
Alpha-particle radiotherapy has gained considerable attention owing to its potent anti-cancer effect. 211At, with a relatively short half-life of 7.2 h, emits an alpha particle within a few cell diameters with high kinetic energy, which damages cancer cells with high biological effectiveness. In this study, we investigated the intravenous injection of 211At-labeled gold nanoparticles (AuNPs) for targeted alpha-particle therapy (TAT). Different kinds of surface-modified gold nanoparticles can be labeled with 211At in high radiochemical yield in 5 min, and no purification is necessary. The in vivo biodistribution results showed the accumulation of 5 nm 211At-AuNPs@mPEG at 2.25% injection dose per gram (% ID/g) in tumors within 3 h via the enhanced permeability and retention (EPR) effect. Additionally, we observed a long retention time in tumor tissues within 24 h. This is the first study to demonstrate the anti-tumor efficacy of 5 nm 211At-AuNPs@mPEG that can significantly suppress tumor growth in a pancreatic cancer model via intravenous administration. AuNPs are satisfactory carriers for 211At delivery, due to simple and efficient synthesis processes and high stability. The intravenous administration of 5 nm 211At-AuNPs@mPEG has a significant anti-tumor effect. This study provides a new framework for designing nanoparticles suitable for targeted alpha-particle therapy via intravenous injection.